Korean species of the genus Perlomyia Banks, 1906 (Plecoptera: Leuctridae) - Murányi, Dávid; Jeon, Mi Jeong; Hwang, Jeong Mi; Seo, Hong Yul (Zootaxa, 2014)
Eight species of the genus Perlomyia (Plecoptera: Leuctridae) are reported from Korea, six are new records for the Korean Peninsula. Two species, known only as unassociated females are described under informal unnamed designations. Previous Korean records are discussed, taxonomic characters of the Korean specimens and Korean distribution are presented for these species. Zoogeographic notes on the Asian Perlomyia are also given.